(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyse the role of management audit systems in increasing sales at Indomaret stores. Management audits are used as an evaluation tool to assess the effectiveness, efficiency, and economy of operational activities, particularly in the sales function. This study uses a qualitative descriptive approach with a focus on examining the management audit process and its implications for sales performance. Research data was collected through direct observation of store operational activities, in-depth interviews with management and employees, and documentation studies related to audit reports, sales data, and standard operating procedures. The data obtained was analysed through data reduction, data presentation, and conclusion drawing stages. The results showed that the implementation of a good management audit system was able to identify various operational weaknesses, such as inventory management, product arrangement, customer service quality, and the level of compliance with SOPs. These audit findings form the basis for management in formulating corrective actions that contribute to improved sales performance. Thus, the management audit system plays an important role as an internal control tool in improving the sales effectiveness and competitiveness of Indomaret stores.